The Determinants of Healthcare Cost for Glaucoma Patients in Cicendo Eye Hospital, Bandung, Indonesia - Rizki, Rahmah Nur; Sihaloho, Estro Dariatno (Media Kesehatan Masyarakat Indonesia, 2020)
Glaucoma is the second foremost cause of impaired vision. People who suffered from Glaucoma face the independent expenditure for the treatment as blind people with Glaucoma could not be cured perfectly. This study intends to analyze the effect of age, types of patient care, types of Glaucoma, and types of payment on the total cost of care of glaucoma patients at Cicendo Eye Hospital, Bandung, Indonesia. This study uses 3,358 patient medical records of Cicendo Eye Hospital, Bandung, Indonesia, in 2018. The 3,358 samples were selected from the patient’s medical record based on patients’ categories indicated or convicted of having Glaucoma. Robust Linear Regression is applied in this study to measure the additional cost for Glaucoma treatment. The results showed that the total cost of patient care was positively and significantly affected by hospitalization status (p=0.000), age (p=0.000), times of treatment (p=0.000), having primary glaucoma (p=0.000), having congenital glaucoma (p=0.000), and presence of intraocular (p=0.000). Conversely, patient care’s total cost was negatively and significantly affected using insurance (p=0.082). This result would be a precautionary measure for the medical institution to consider better financial planning, service delivery improvement, and the patient’s payment scheme effectiveness.